Quantifying the most intense periods of match-play in rugby union - Howe, S. T.; Aughey, R.; Hopkins, W. G.; Cavanagh, B.; Duthie, G.; Stewart, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Understanding match activity profiles may guide training prescription and in-game decision making. Peak periods of activity can be quantified via the mean value in a moving window of a given duration. This approach was applied here to National rugby union matches. METHODS: Movement data were collected via global positioning system and accelerometry for the 30 players of an Australian National Rugby Championship team across the eight matches of a season. Mean running speed (m.min-1), external load (PlayerLoad (TM)) and metabolic power were analysed using a rolling average method to identify the maximum mean values for periods ranging from 5 s to 10 min. General linear mixed modelling was used to predict these measures, with fixed effects for positional differences (backs, forwards), match half (1st, 2nd), and within-season trend (date as linear numeric), and with random effects for between-player differences, within-player variabilities, and between-match differences. The random effects were combined into intraclass correlation coefficients representing reproducibility of each measure. Effects were quantified using standardization and interpreted with magnitude-based inferences. RESULTS: There was an approximately six-fold reduction in mean running speed for the longest window duration compared with the shortest. Backs achieved clearly faster speeds than forwards by 21% (90% confidence limits ±9%) for the 5-s window down to 1.5% (±7.5%; unclear) for the 10-min window. Mean running speed declined clearly by up to 11% in the second half for forwards and backs for most windows of 1 min. Mean running speed declined clearly by ~7% over the season for windows of 5 min for backs and by 9-14% for windows 30 s for forwards. The reproducibility of mean running speed between halves and between matches was poor for the 10-min window (ICC=0.54) and very poor for the shorter windows (ICC <0.50). External load and metabolic power showed effects generally similar to those of mean running speed, but external load was clearly higher for forwards over the 10-min window, and reproducibility of external load was impractical (ICC <0.20) for all but the 10-min window (ICC=0.51). DISCUSSION: The differences and changes in the mean measures of maximumintensity match play have direct implications for design of training and for substitution decisions of professional rugby union players. The low reproducibility of the measures implies that players will have to be monitored across many games to obtain adequate precision for assessing physical performance of individual players.